Assessment of pharmacokinetic interaction between rilotumumab and epirubicin, cisplatin and capecitabine (ECX) in a Phase 3 study in gastric cancer. (13th December 2016) - Zhang, Yilong; Kuchimanchi, Mita; Zhu, Min; Doshi, Sameer; Hoang, Tien; Kasichayanula, Sreeneeranj
Abstract : Aims: Rilotumumab is a fully human monoclonal antibody investigated for the treatment of MET‐positive gastric cancer. The aim of this study was to evaluate the potential pharmacokinetic (PK)‐based drug–drug interaction (DDI) between rilotumumab and epirubicin (E), cisplatin(C) and capecitabine (X). Methods: This was a Phase 3 double‐blind, placebo‐controlled study, in which rilotumumab, epirubicin and cisplatin were administered intravenously at 15 mg kg −1, 50 mg m −2, and 60 mg m −2 Q3W, respectively, while capecitabine was given orally at 625 mg m −2 twice daily. Rilotumumab PK samples were taken at pre‐dose and at the end‐of‐infusion from all patients in cycles 1, 3, 5 and 7. ECX PK samples were taken in cycle 3 from patients who participated in the intensive PK assessment. ECX PK was assessed by non‐compartmental (NCA) analyses and PK parameters were compared between two arms. Rilotumumab PK was assessed by comparing the observed rilotumumab serum concentrations with model‐predicted concentrations using a population PK model developed from previous Phase 1 and Phase 2 studies. Results: The study enrolled 609 patients. ECX plasma concentrations in the presence and absence of rilotumumab were similar, as demonstrated by the geometric mean ratios for C max and AUC, which were close to 1.0, suggesting ECX PK was not affected by co‐administration of rilotumumab. The observed rilotumumab serum concentrations were similar to the values predicted by population PK modelling on the basis of a prediction‐corrected visual predictive check, indicating rilotumumab exposure was not affected by co‐administration of ECX. Conclusions: The results suggest lack of PK‐based DDI between rilotumumab and ECX.